Conditions of training activity and health in complex coordination sports - Kogan O.S.; Yamileva R.M.; Greb A.V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the conditions of training activity and the health status of high-class athletes in complex coordination sports in order to justify appropriate measures to monitor their health and complete medical rehabilitation. Methods and structure of the study. An analysis of the hygienic indicators of the conditions of training activities in complex coordination sports was carried out using the example of gymnastics classes by high-class athletes from the School of Higher Sports Excellence of the Republic of Bashkortostan. The state of health and functional disorders of women, representatives of artistic gymnastics, was analyzed based on the results of an in-depth medical examination performed by specialists of the Republican Medical and Physical Education Dispensary of the Republic of Bashkortostan. Results and conclusions. Analysis of scientific literature and the authors’ own research indicates that in the process of sports activity, athletes are or can be influenced by a complex set of factors in the working environment and the labor (training) process, similar to those when working in harmful and/or dangerous working conditions. According to the authors, the systematic impact of unfavorable factors in sports activity against the background of chronic fatigue, characteristic of highly qualified athletes, is accompanied by cumulative effects in the form of functional changes of both an adaptive and maladaptive nature, and can cause the occurrence of somatic pathology.